Digital Vector in Global Educational Policy: Will it Ensure Social Justice and Access to Education? - E. A. Antyukhova; P. I. Kasatkin (Vestnik MGIMO-Universiteta)
Abstract: Ensuring the accessibility of education based on the development of online learning as one of the tasks of the global educational policy is acquiring key importance today. This task is complicated by different levels of economic development of countries and digital divide, problems of modernization of national education systems in the context of the spread of IT technologies. The development of education is closely related to technological advances (artificial intelligence, augmented and virtual reality, robotics), but such changes are not actively manifested in education due to its conservatism, and are also associated with the level of development of countries and access to new technologies for citizens. An analysis of investment activity in the education sector shows that investors are wary of financing the development of education and, in particular, online education, but trends over the past five years show a fourfold increase in total investment. The article concludes that: 1) despite the emergence of both universal and specialized educational online platforms, they cannot create an individual trajectory for acquiring knowledge and mastering competencies, as this can still be done on the basis of classical university education; 2) online platforms broadens the choice among the many offered educational programs and courses, however objectivity of this choice tends to be decreasing.